Pengaruh Media Sosial, Lokasi, Store Atmosphere terhadap Niat Beli di Cafe - Sulistiyawati Sulistiyawati (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
This study aims to determine and analyze the influence of social media, location, store atmosphere on purchase intention at the friend's cafe in Sampang. This type of research is quantitative research using a conclusive classification: data collection techniques using non-probability sampling classification and judgmental techniques. The number of samples used in this study was as many as 100 respondents who knew and had accessed the Instagram account of Teman Sehati café. The analysis technique uses multiple linear regression analysis with the SPSS version 25 program. The results show that social media positively and significantly affect purchase intention at Teman Sehati cafe in Sampang. There is a significant influence of location on purchase intention at the Teman Sehati cafe Sampang; the store atmosphere has a positive and significant effect on the purchase intention of a Teman Sehati café in Sampang. Café Teman Sehati is expected to be able to design outlets in such a way as to increase customer convenience with a positive store atmosphere. In addition, it is expected to consider the location to increase consumer purchase intention. Further research can use newer variables such as convenience, promotion, or service quality.